ANDROID BASED SYAIR APPLICATION AS AN OLD LITERATURE TEACHING INNOVATION IN THE DIGITAL ERA - Wulandari, Yosi; Purwanto, Wachid Eko; Effendi, Muh Saeful; Sulistiyono, Roni; Fisari, Nika (Balai Bahasa Sumatra Barat, 2022)
As one of Indonesian original literary works, Syair needs to be introduced and taught proportionally. Unfortunately, in the implementation of teaching, syair still meets some constrains, including (1) Indonesian language textbooks in junior high schools contain only a small amount of material on syair. (2) syair teaching is focused on cognitive competence, so it is not attractive. (3) syair teaching material only provides the definition, the elements, and limited examples. (4) there is no digital-based teaching material specifically for syair that is used as teaching material. (5) the teacher found difficulty providing examples on how to read syair according to the song or venom. Therefore, it is necessary to develop digital-based teaching materials in syair teaching. This research uses the Research Development method developed by Borg and Gall. The research stage that has been carried out in the development stage and the teaching materials' feasibility test. Based on the feasibility test results on the Syair application, it can be concluded that this application is feasible to be applied to Class VII SMP students. In addition, based on the validator's assessment, the limited trial and large class of this application in terms of material and learning is appropriate and feasible to use to meet students' needs in learning and mastering syair.Keywords: It consists of maximum five words/phrases typed in bold style.